Snake Venom Cathelicidins as Natural Antimicrobial Peptides - de Barros, Elizângela; Gonçalves, Regina M.; Cardoso, Marlon H.; Santos, Nuno C.; Franco, Octávio L.; Cândido, Elizabete S. (Frontiers in Pharmacology, 2019)
Bioactive small molecules isolated from animals, plants, fungi and bacteria, including natural antimicrobial peptides, have shown great therapeutic potential worldwide. Among these peptides, snake venom cathelicidins are being widely exploited, because the variation in the composition of the venom reflects a range of biological activities that may be of biotechnological interest. Cathelicidins are short, cationic and amphipathic molecules. They play an important role in host defense against microbial infections. We are currently facing a strong limitation on pharmacological interventions for infection control, which has become increasingly complex due to the lack of effective therapeutic options. In this review, we will focus on natural snake venom cathelicidins as promising candidates for the development of new antibacterial agents to fight antibiotic resistant bacteria. We will highlight their antibacterial and antibiofilm activities, mechanism of action and modulation of the innate immune response.